An Error Analysis on The Use of Simple Past Tense on The Student’s Narrative Writing Ability at Class XI.1 Madrasah Aliyah Nurul Falah Airmolek - Puja Arismawati; Loly Novita; Destri Wahyuningsih (Indonesian Journal Publisher, 2025)
A descriptive qualitative method was used to analyze grammatical errors in the use of the simple past tense in narrative writing by 25 students of class XI.1 at Madrasah Aliyah Nurul Falah Airmolek. The students were assigned to write a narrative text about “An Unforgettable Holiday,” and their works were examined using the Surface Strategy Taxonomy by Dulay, Burt, and Krashen, covering omission, addition, misformation, and misordering. The analysis identified 157 total errors, with misformation (67.52%) as the most dominant, followed by omission (22.93%), misordering (6.37%), and addition (3.18%). These results indicate that students have difficulty with verb formation, auxiliary usage, and sentence structure. The causes of these errors include first language interference, overgeneralization of rules, limited exposure to correct written input, and insufficient feedback during learning activities. These findings demonstrate the crucial role of explicit grammar teaching, along with structured writing tasks that allow students to apply their understanding in meaningful contexts. Incorporating peer editing and teacher-led error correction is also essential in minimizing recurring mistakes. In addition, the importance of reinforcing regular and irregular verb patterns through focused instruction should be emphasized in classroom practice. These strategies are expected to help students internalize the appropriate use of past tense in written English. This study contributes to the field of language education by highlighting the persistent grammatical issues faced by learners and offering pedagogical recommendations for improvement. Future research may expand the scope by comparing grammatical errors across different text genres or proficiency levels